2011
DOI: 10.1002/jmr.1114
|View full text |Cite
|
Sign up to set email alerts
|

AFM imaging of extracellular polymer release by marine diatom Cylindrotheca closterium (Ehrenberg) Reiman & J.C. Lewin

Abstract: Extracellular polysaccharide production by marine diatoms is a significant route by which photosynthetically produced organic carbon enters the trophic web and may influence the physical environment in the sea. This study highlights the capacity of atomic force microscopy (AFM) for investigating diatom extracellular polysaccharides with a subnanometer resolution. Here we address a ubiquitous marine diatom Cylindrotheca closterium, isolated from the northern Adriatic Sea, and its extracellular polymeric substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 49 publications
7
57
0
Order By: Relevance
“…Pletikapic et al (2011) confirmed the surface morphology of EPS isolated from Cylindrotheca closterium appeared as networks at 10 μg/ml. The AFM image of EPS from Amphidinium carterae appeared as different particle sizes, with 181 nm average roughness (Mandal et al, 2011).…”
supporting
confidence: 69%
“…Pletikapic et al (2011) confirmed the surface morphology of EPS isolated from Cylindrotheca closterium appeared as networks at 10 μg/ml. The AFM image of EPS from Amphidinium carterae appeared as different particle sizes, with 181 nm average roughness (Mandal et al, 2011).…”
supporting
confidence: 69%
“…However, the segments forming the network shown in Figure 9c are significantly wider (50 vs. 140 nm), suggesting side-by-side associations once the maximum height of individual fibrils is reached. If we take the value of 2.6 nm observed using AFM analysis as the maximum fibril height, then up to six monomolecular fibrils can constitute a single polysaccharide fibril [79]. The absence of globules in the AFM images of isolated polysaccharides also indicates that the globules, which appeared as a constitutive component in the EPS of single cells (Figures 9b,c), are not polysaccharides.…”
Section: Extracted and Purified Polysaccharides Of C Closteriummentioning
confidence: 97%
“…Protocols for marine sample AFM imaging have been developed only recently: single diatom cells and released polymers [79]; isolated polysaccharides from diatom cultures [3,79]; marine gel polymers and networks [80]. The samples were prepared using the drop deposition method (5-10 µL aliquots) and mica as a substrate.…”
Section: The Supramolecular Organization Of Polysaccharide Fibrils: Fmentioning
confidence: 99%
“…The force was kept at the lowest possible value in order to minimize the forces of interaction between the tip and the surface. Measurements were performed in air, at room temperature and 50-60 % relative humidity, which leaves the samples with a small hydration layer, helping to maintain the structure [26] using freshly cleaved mica as a substrate. All images are presented as raw data except for the first-order two-dimensional flattening.…”
Section: Sample Preparation For Afm Imaging and Afm Measurementsmentioning
confidence: 99%